Learning Strategies using Fun Learning Methods for Early Childhood Education at biMBA AIUEO, Tangerang Regency - Dyatmika, Jingga Kenya; Hastut, Isnaini Budi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Objective: This study aims to describe the implementation strategy of the Fun Learning Method used in biMBA AIUEO, a non-formal early childhood education institution (PAUD) in Indonesia. This research specifically explores how the institution's main pedagogical pillars, the Individual System and the Small Step System, are used to foster Learning Interest (intrinsic learning interest).Methodology: This study uses a descriptive qualitative design. Data was collected at the biMBA AIUEO branch in Tangerang Regency through triangulation, including semi-structured interviews with senior motivators (teachers), direct observation without participation in class activities, and documentation analysis of exclusive learning modules (known as tickets). Data are analyzed using a thematic analysis approach to identify and describe core strategies. Results: The findings show a systematic pedagogical model in which Fun Learning becomes the basic philosophy. This philosophy is implemented through two interrelated methods: the Individual System, which is aligned with Gardner's Theory of Multiple Intelligences by tailoring teaching according to each child's unique character, and the Small Step System, which serves as a practical application of Vygotsky's Proximal Development Zone (ZPD) by providing gradual and sequential guidance. Teacher Variation Skills are used to manage children's emotions to stay in a positive state that supports the learning process. Application/Authenticity/Value: This study provides a rare and practical bridge between established Western pedagogical theories (Constructivism, MI, ZPD) and the unique and scalable Early Childhood Education (PAUD) model in Indonesia. The study offers a valuable and field-tested framework for educators and policymakers who want to apply the child-centered, play-based principles of the Indonesian Merdeka Curriculum.